The effects of projects of dredging and recovering saline sand at estuaries in Binh Thuan - Ninh Thuan provinces - Trung, Pham Ba; Mau, Le Dinh; Binh, Tran Van (Vietnam Journal of Marine Science and Technology, 2019)
According to statistics in Binh Thuan - Ninh Thuan provinces, there are 4 projects of dredging and recovering saline sand at estuaries such as La Gi, Ca Ty, Phan Ri Cua and Dong Hai. These projects use dredging plans by sand suction vessel and scraper bucket to scoop sand on barges, then sand is transferred to ships for exportation or used for levelling platform of urban buildings on the south bank of estuaries. The channel dredging process has changed and distributed the energy of waves, currents, tides, dynamics, incident wave fields, geological structures, topographic characteristics of the shore and bottom, thereby forming the new erosion - deposition process, affecting the shoreline in estuaries